2011
DOI: 10.1590/s0103-65642011005000004
|View full text |Cite
|
Sign up to set email alerts
|

Assimetrias hemisféricas na percepção de expressões faciais: um estudo com a técnica de campo visual dividido

Abstract: Resumo: Foram investigadas as diferenças hemisféricas na percepção de expressões faciais de alegria, tristeza, raiva e medo. Vinte e um voluntários (9H, 12M) participaram do experimento. Foi utilizada a técnica de estudo campo visual dividido com a apresentação de faces à esquerda e à direita do ponto de fixação nas condições: 1) face com emoção à esquerda e face neutra à direita; 2) face neutra à esquerda e face com emoção à direita; 3) face com emoção à direita e à esquerda; 4) face neutra à direita e à esqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The present results are also in agreement with the findings of Tamietto et al . () and Torro‐Alves, de Sousa, and Fukusima () that, presenting explicit emotional faces bilaterally to healthy subjects, found better performance with emotional stimuli presented in the LVF, mainly when they were negative.…”
Section: Discussionmentioning
confidence: 90%
“…The present results are also in agreement with the findings of Tamietto et al . () and Torro‐Alves, de Sousa, and Fukusima () that, presenting explicit emotional faces bilaterally to healthy subjects, found better performance with emotional stimuli presented in the LVF, mainly when they were negative.…”
Section: Discussionmentioning
confidence: 90%
“…As mentioned above, however, the results of the majority of studies have tended to interpret their laterality results as exclusively in favor of either the VH or the RHH. For example, asked participants to recognize a target emotion in a divided visual field paradigm in which the target and a distracting expression were simultaneously presented, finding that emotional targets were better and faster recognized when presented in the left visual field, supporting the RHH (Torro-Alves et al, 2011). In contrast, Jansari et al ( 2Q4 011), using a similar paradigm, found support for the VH, since positive emotions were better recognized when presented in the right visual field (RVF) and negative emotions were better recognized when presented in the left visual field (LVF).…”
Section: Introductionmentioning
confidence: 80%
“…By using a similar lateralized presentation, different results have been collected. For instance, Torro-Alves, de Sousa, and Fukusima (2011) asked participants to recognize a target emotion in a paradigm in which the target and a distracting expression were simultaneously presented. The authors found that emotional targets were better and faster recognized when presented in the LVF, supporting the RHH.…”
mentioning
confidence: 99%